2014
DOI: 10.1007/s12311-014-0617-9
|View full text |Cite
|
Sign up to set email alerts
|

What Does Low-Intensity rTMS Do to the Cerebellum?

Abstract: Non-invasive stimulation of the human cerebellum, such as by transcranial magnetic stimulation (TMS), is increasingly used to investigate cerebellar function and identify potential treatment for cerebellar dysfunction. However, the effects of TMS on cerebellar neurons remain poorly defined. We applied low-intensity repetitive TMS (LI-rTMS) to the mouse cerebellum in vivo and in vitro and examined the cellular and molecular sequelae. In normal C57/Bl6 mice, 4 weeks of LI-rTMS using a complex biomimetic high-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
(22 reference statements)
2
22
1
Order By: Relevance
“…Since our previous studies suggest that low intensity magnetic stimulation has less effect on normal vs. abnormal neural circuits (Rodger et al, 2012; Sykes et al, 2013; Makowiecki et al, 2014), we lesioned our explants to create a denervation/reinnervation model. Cerebellar plates were separated from their explant brainstem at DIV 23 (equivalent to P17), placed adjacent to intact cerebellar tissue of a second explant (co-culture; Figures 1A,D,E and 2D ) and stimulated to induce reinnervation (Morellini et al, 2015). …”
Section: Methods and Results: Stimulation Device Design Constructionmentioning
confidence: 99%
“…Since our previous studies suggest that low intensity magnetic stimulation has less effect on normal vs. abnormal neural circuits (Rodger et al, 2012; Sykes et al, 2013; Makowiecki et al, 2014), we lesioned our explants to create a denervation/reinnervation model. Cerebellar plates were separated from their explant brainstem at DIV 23 (equivalent to P17), placed adjacent to intact cerebellar tissue of a second explant (co-culture; Figures 1A,D,E and 2D ) and stimulated to induce reinnervation (Morellini et al, 2015). …”
Section: Methods and Results: Stimulation Device Design Constructionmentioning
confidence: 99%
“…For example, antidepressant medications, ECT, and rTMS have all been reported in human and animal models to increase the expression and signaling of brain‐derived neurotrophic factor (BDNF, a trophic factor that mediates neuroplasticity) in the hippocampus and cortex . Repetitive TMS has been demonstrated to enhance neuroplasticity in cortical and corticospinal systems, possibly mediated through changes in expression of BDNF . Increased BDNF (either through direct injection into the brain or overexpression through transgenic manipulation) can produce changes in behavior similar to those induced by antidepressant medications .…”
Section: Antidepressant Treatments May Exert Similar Actions At Diffementioning
confidence: 99%
“…[28][29][30] Repetitive TMS has been demonstrated to enhance neuroplasticity in cortical and corticospinal systems, possibly mediated through changes in expression of BDNF. [30][31][32] Increased BDNF (either through direct injection into the brain or overexpression through transgenic manipulation) can produce changes in behavior similar to those induced by antidepressant medications. 33,34 Increased BDNF expression may be induced by epigenetic processes, such as chromatin remodeling and histone methylation; alterations in intracellular signaling, such as phosphorylation of transcription factors affecting gene expression; and posttranslational modification of proteins.…”
Section: Antidepressant Treatments May Exert Similar Actions At Diffementioning
confidence: 99%
“…Impairments in the activation function of the synaptic transmission between the climbing bres and Purkinje cells inhibits cortical motor activation via a complex neural pathway involving the dentate nucleus, which could be related to abnormal postural sways in SCA3 patients [37][38] . Previous studies have demonstrated that cerebellar transcranial magnetic stimulation (TMS) is capable of facilitating motor cortical activation via modulation of Purkinje cell excitability [39][40] . Therefore, TMS is recommended to activate the function of the cerebellar to improve balance.…”
Section: Discussionmentioning
confidence: 99%